Thursday

July 31, 2014

July 31, 2014

Posted by **kori** on Wednesday, January 2, 2013 at 11:18pm.

- math -
**Anonymous**, Thursday, January 3, 2013 at 3:52am( x - 2 ) ( x + 2 ) =

x ^ 2 - 2 x + 2 x - 4 =

x ^ 2 - 4 =

- ( x ^ 2 - 4 ) =

4 - x ^ 2

So :

4 - x ^ 2 = - ( x - 2 ) ( x + 2 )

**Related Questions**

Math-Help asap please~ - For each function, the point given is the maximum or ...

math - simplify the difference quotient: f(x+h)-f(x), (h ≠ 0) as much as ...

Algebra - Find the difference quotient: f(x+h)-f(x)/h for f(x) = 4x-9 and ...

Algebra - Please Find the difference quotient f(x+h)-fx/h for f(x)= 4x-9 and ...

Algebra - My problem is compute and simplify the difference quotient f(x+h)-f(x...

Calculus AP - i wanna KNOW IF im DOING RIGHT. Evaluate the difference quotient ...

precalculus - Write and simplify the difference quotient for the function b(t)= ...

Pre-Calculus - Using the difference quotient to find M-sec for h=0.5 at x=1. f(...

Pre-Calculus - Using the difference quotient find M-sec for h=0.5 at x=1. f(x)=...

Math - Simplify the difference quotient [f(2 + h) − f(2)]/h if h ≠ 0...